Assessing the use of methotrexate as an alternate therapy for pemphigus vulgaris and pemphigus foliaceus. Issue 8 (1st July 2022) - Kolla, Avani; Shah, Payal; Cymerman, Rachel; Fruchter, Renee; Adotama, Prince; Soter, Nicholas A.
Abstract: Methotrexate is historically recognized as an effective treatment of pemphigus but its utility as a single or alternate steroid‐sparing agent was not recognized in recent consensus recommendations in pemphigus management. We aimed to evaluate the efficacy and safety of a treatment course for pemphigus that involves methotrexate as a single or steroid‐sparing agent. In a retrospective cohort study, we examined patients with pemphigus vulgaris or pemphigus foliaceus who were on ≥3 months of methotrexate therapy. Efficacy and safety were evaluated by established pemphigus disease endpoints. Of the 34 patients who met inclusion criteria, 25 (73.5%) were on glucocorticoids at time of methotrexate initiation (median follow‐up: 5.4 years; median time on methotrexate: 3.7 years). An appreciable proportion achieved disease control (91.2%), with some achieving clinical remission off all systemic therapies (23.5%). For patients on glucocorticoids, median time to control was 42 days, median time to minimal steroid dose tapering (5 mg prednisone) was 161 days, and median time to complete steroid tapering was 308 days. For patients on methotrexate as a single agent, median time to control was 119 days. Among all patients, relapse commonly occurred (88.2%). At last follow‐up, 26.5% were managed on topical therapies alone and 11.8% required systemic steroid therapy. Methotrexate was largely tolerated with a low incidence of adverse events leading to treatment discontinuation (2.9%). Methotrexate has the potential to be an effective and well‐tolerated option for patients and may be considered for use as an alternate single or steroid‐sparing agent for pemphigus.